LEGALITAS PENDIRIAN PERSEROAN PERORANGAN: ANALISIS SINERGI ANTARA UU CIPTA KERJA, UU PERSEROAN TERBATAS, DAN IMPLEMENTASI PERATURAN MENTERI HUKUM DAN HAM NOMOR 21 TAHUN 2021 - Wisnu Ardytia (UNTAG Law Review, 2025)
AbstractThis study examines the legality of establishing a Sole Proprietorship Corporation in the era of regulatory reform through the implementation of Law No. 6 of 2023 on Job Creation, which offers an alternative for creating legal entities with single ownership. It further explores its relationship with the traditional legal framework as stipulated in Law No. 47 of 2007 concerning Limited Liability Companies. The research analyzes the fundamental principles of company establishment—such as freedom of enterprise, transparency, legal protection, and accountability—and observes how these principles are integrated into operational practices through the Regulation of the Minister of Law and Human Rights No. 21 of 2021 regarding the Requirements and Procedures for Registration, Amendment, and Dissolution of Legal Entities of Limited Liability Companies in conjunction with Law No. 6 of 2023 on Job Creation. The findings indicate that the regulatory innovations introduced by the Job Creation Law have created opportunities to enhance bureaucratic efficiency and attract investments by streamlining the establishment process. However, the implementation also faces challenges, including bureaucratic cultural adaptation, digital infrastructure disparities, and the necessity for a deeper understanding of corporate legal principles among business actors and government officials. The study concludes that synergy among these three regulatory frameworks is essential for fostering a more dynamic, transparent, and accountable business environment, thereby supporting national economic growth in a globally dynamic context.